(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: ureterorenoscopy; pneumatic lithotripsy; ureteric stone; spinal anaesthesis doi: 10.3329/jcmcta.v19i1.3844 Journal of Chittagong Medical College Teachers’ Association 2008: 19(1):11-14